FOXO3 polymorphisms influence the risk and prognosis of rhabdomyosarcoma in children - Zhang, Xiaohong; Sun, Yaping; Niu, Huilin; Tan, Ping; Liu, Shanshan; Liu, Xiaoping; Liu, Xiaodan; Luo, Ailing; Cai, Mansi; Yan, Yaping; Xu, Ling; Yang, Xu (Frontiers in Oncology, 2024)
Background: Rhabdomyosarcoma(RMS) is the most common soft tissue sarcoma in children and single nucleotide polymorphisms(SNPs) in certain genes influence risk of RMS.Although FOXO3 had been reported in multiple cancers including RMS, the role of FOXO3 polymorphisms in RMS remains unclear. In this case-control study, we evaluated the association of FOXO3 SNPs with RMS risk and prognosis in children.Methods: Four FOXO3 SNPs(rs17069665 A>G, rs4946936 T>C, rs4945816 C>T and rs9400241 C>A) were genotyped in 110 RMS cases and 359 controls. The associations between FOXO3 polymorphisms and RMS risk were determined by odds ratios(ORs) with 95% confidence intervals(CIs). The associations of rs17069665 and rs4946936 with overall survival in RMS children were estimated using the Kaplan-Meier method and log-rank test.Functional analysis in silico was performed to estimate the probability that rs17069665 and rs4946936 might influence the regulation of FOXO3.We found that rs17069665 (GG vs. AA+AG, adjusted OR=2.96;; P=0.010) and rs4946936 (TC+CC vs. TT, adjusted OR=0.48; 95%CI [0.25-0.90]; P=0.023) were related to the increased and decreased RMS risk, respectively. Besides, rs17069665(P<0.001) and rs4946936(P<0.001) were associated with decreased and increased overall survival in RMS patients, respectively. Functional analysis showed that rs17069665 and rs4946936 might influence the transcription and expression of FOXO3 via altering the bindings to MYC, CTCF, and/or RELA.This study revealed that FOXO3 polymorphisms influence the RMS susceptibility and prognosis in children, and might altered the expression of FOXO3. FOXO3 polymorphism was suggested as a biomarker for RMS susceptibility and prognosis.